Pengaruh Penggunaan Firewall Generasi Terbaru (NGFW) terhadap Tingkat Keamanan Jaringan di Koperasi Sekolah Bina Mulia (KSBM) - Asep Ramdhani Mahbub; Dwi Budi Srisulistiowati (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
The rapid development of information technology has encouraged cooperatives to manage network and customer data digitally. Bina Mulia School Cooperative (KSBM) is one such cooperative that has intensive network activities, including savings and loan services and the sale of office supplies. The increase in traffic and variety of cyber threats such as malware, phishing, ransomware, as well as application-based attacks, has made traditional firewalls insufficient. Next-Generation Firewalls (NGFW) have emerged as a solution with capabilities such as deep packet inspection, intrusion detection, application control, and threat intelligence integration. This study aims to analyze the impact of using NGFW on the network security level at KSBM. The research uses a quantitative approach with a survey method involving 50 respondents from the IT unit, administrative staff, teachers, and students who use the cooperative's network services. The data were analyzed using simple linear regression to examine the effect of variable X (implementation of NGFW) on variable Y (network security level). The study results showed that the use of NGFW has a positive and significant impact on network security, with an R value of 0.812 and an R² value of 0.660. This indicates that 66% of the improvement in network security is influenced by the quality of NGFW implementation. Thus, NGFW has been proven to enhance threat detection, prevent attacks, and reduce the risk of data breaches at Bina Mulia School Cooperative (KSBM).